GERAKAN EKOLOGI DALAM KEHIDUPAN MASYARAKAT MUSLIM-SAMIN: Studi Living Qur’an di Desa Tegaldowo Gunem Rembang - M. Zaenal Arifin (STAI AL-ANWAR SARANG, 2020)
This article is a study of the traditions and ecological movements of the Samin Muslims community in Tegaldowo village, Gunem sub-district, Rembang based on the living Quran. The ecological traditions and movements that occur in the life of the Samin Muslims community are appealing to study, because apart from being a ‘hybrid society’ that uses the Quran in their society, they also describe the meaning of Quran in a local approach. The formulation of the issuedemonstrated in this study is how the Samin Muslims community uses Quran and absorbs the Quran in their ecological movement. This research is a descriptive field research type using a sociological approach to religion. Data collection was carried out by engaging observation, in-depth interviews, and documentation. This study found that the Samin Muslims community in Tegaldowo village has their own way of maintaining natural stability with the result that their relationship with various sub-systems or other environmental components is well balanced. They carry out an ecological movement by reading the Surah al-Ikhlaṣ as much as four thousand four hundred and forty-four times to be collated with the rituals inherited from their ancestors, that to maintain harmony with nature as well as a form of resistance to the exploitation of nature. Ecological movements and cultural activities such as the brokohan are combined with Islamic teachings in accordance with the Quran.By that way, cultural acculturation in Tegaldowo village can be developed harmoniously without aborting the old culture that has been developed in the traditions of Javanese society